2020
DOI: 10.3390/jof6040201
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the Candida haemulonii Complex to Echinocandins: Focus on Both Planktonic and Biofilm Life Styles and a Literature Review

Abstract: Candida haemulonii complex (C. haemulonii, C. duobushaemulonii and C. haemulonii var. vulnera) is well-known for its resistance profile to different available antifungal drugs. Although echinocandins are the most effective class of antifungal compounds against the C. haemulonii species complex, clinical isolates resistant to caspofungin, micafungin and anidulafungin have already been reported. In this work, we present a literature review regarding the effects of echinocandins on this emergent fungal complex. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Previously, our group reported that biofilms formed by clinical isolates of the C. haemulonii complex were susceptible to caspofungin and micafungin [ 45 ], demonstrating that echinocandins can still be considered a treatment option to infections caused by these yeasts. Additionally, echinocandins has also been reported to be active against biofilms formed by C. albicans , C. parapsilosis and C. glabrata , but not against C. tropicalis , evidencing that the differences in action can be related to species-specific characteristics [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, our group reported that biofilms formed by clinical isolates of the C. haemulonii complex were susceptible to caspofungin and micafungin [ 45 ], demonstrating that echinocandins can still be considered a treatment option to infections caused by these yeasts. Additionally, echinocandins has also been reported to be active against biofilms formed by C. albicans , C. parapsilosis and C. glabrata , but not against C. tropicalis , evidencing that the differences in action can be related to species-specific characteristics [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, species of the C. haemulonii complex can form biofilms of different biomasses on several types of catheter surfaces, including vascular (polystyrene), urinary (siliconized latex), nasoenteric (polyurethane), and nasogastric (polyvinyl chloride) catheters [41]. Although the structure and function of biofilms formed by the C. haemulonii species complex have been described, the underlying mechanisms of biofilm formation in these species remain unclear [23,41,45,46]. In general, the abilities to undergo phenotypic transitions and to form biofilms are important in the environmental adaptation and virulence of the C. haemulonii species complex.…”
Section: Biologymentioning
confidence: 99%
“…The reports describe original research in the area of antimicrobials and include work involving individual and combinatorial efficacy of compounds with specific activity against fungi, bacteria, or both within polymicrobial biofilms [6], a screen of a small molecule library alone or in combination with current antifungals in search of compounds with antibiofilm and pre-formed biofilm activities [7], characterization of the effect of echinocandins against planktonic and biofilm lifestyles of clinical isolates from the Candida haemulonii complex [8], and the use of a membranotropic peptide to disrupt polymicrobial biofilms of Candida albicans and Klebsiella pneumoniae [9]. Additional reports phenotypically characterized colonies from Candida parapsilosis clinical isolates as a way to predict their biofilm formation capabilities [10], conducted analyses of the biofilm matrix composition from the Candida haemulonii species complex [11], and investigated the virulence and biofilm capabilities of an Aspergillus fumigatus environmental isolate with interest in the role of this isolate in the textile industry [12].…”
mentioning
confidence: 99%